A study of HPLC patterns in patients of sickle cell anemia with analysis of red cell parameters - Jawarkar, Ashish; Bhatia, Varsha (International Journal of Research in Medical Sciences, 2018)
Background: Sickle cell disease (SCD) and its variants are genetic disorders resulting from the presence of a mutated form of hemoglobin, hemoglobin S (HbS). In this study we want to profile various types of haemoglobins and their relative percentage in sickle cell cases. Also, we will analyse RBC indices such as Hb, HCT, MCV, MCH, MCHC and RDW-CV. Methods: We analysed blood from 200 patients suspected to have Sickle cell hemoglobinopathies and subjected it to Sickling screening test. All positive cases will be subjected to HPLC to separate constituent haemoglobins and CBC analysis was done to check RBC indices. Results: In sickle cell trait (SCT) patients, there is a significantly higher level of HbA2 and HbS and significantly lower level of HbA. In sickle cell disease patients, there were significantly higher levels of HbA2, HbF and HbS and significantly lower levels of HbA. Both sickle cell trait and sickle cell disease patients had significantly lower levels of haematocrit, MCH and higher RDW CV. Conclusions: While analysing HPLC patterns, appearance of HbS, low levels of HbA and high levels of HbF and HbA2 should raise a suspicion for presence of Sickle cell hemoglobinopathy. There was statistical difference in levels of Hb, HCT, MCH and RDW-CV between cases and controls. High index of suspicion should be maintained when these parameters are on lower side, especially in population who is prone to have sickle cell disorders.